Clinical diagnosis of dengue hemorrhagic fever in children - Rosyid Rosyid; R. A. Nelwan; Sutrisno D. S.; Teluk Sebodo; Ismangoen Ismangoen (Paediatrica Indonesiana, 1981)
Investigation on 111 patients clinically suspected suffering from Dengue Haemorrhagic Fever (DHF) admitted to the Department of Child Health, University of Gudjah Mada Hospital, was conducted. Laboratory examination of peripheral blood consisting of platelet count, hematocrit, and W BC count, aswell as serologic examination for DHF were performed. The results of serologic examination showed that 56 out of 111 patients were found 10 be positive for DHF. The results showing the relationship between peripheral blood examination and serologic examination from those 56 patients are as follows: Group I (patients without thrombocytopenia, leucopenia, and haemoconcentration) consisted of 31 patients all of them showed negative results on serologic examination. Group II (patients with only thrombocytopenia) consisted of 8 patients, only one patient (12.5%) was found serologically positive. Group III (patients with thrombocytopenia and haemoconcentration) consisted of 15 patients, 14 patients (93.3%) were found serologically positive. Group IV (patients with thrombocytopenia and leucopenia) consisted of 11 patients, 9 patients (81.8%) were found serologically positive. Group V (patients with thrombocytopenia, hemoconcentration and leucopenia) consisted of 32 patients, all of them were found serologically positive. The calculalion of sensitivity and specificity ill grouping the patients on the basis of laboratory symptoms showed that: Group III sensitivity = 93.5% and specificily = 87.5%; Group IV sensitivity=90% and specificity=77.7%; Group V sensitivity=6.9.% and specificity=100%.